Evaluating approaches for integrating species distributions in spatial conservation planning - Jason M. Winiarski; Amy A. Shipley; Drew N. Fowler; Matthew D. Palumbo; Jacob N. Straub (Conservation Science and Practice)
Abstract Map‐based decision support tools (DSTs) that use species distributions are an important means of identifying priority areas for conservation. The Wisconsin Waterfowl Habitat Conservation Strategy (WWHCS) uses a DST to identify priority ecological landscapes and watersheds to guide waterfowl habitat projects. The WWHCS DST relies on waterfowl habitat suitability layers derived through expert opinion in lieu of species distributions, a common approach in DSTs. Given the subjectivity of expert opinion, model‐driven species distributions such as those available from community science projects could provide more reliable information and better identify areas for waterfowl conservation. Here, we explore the application of relative abundance products available through the eBird Status and Trends project as an alternative to expert‐derived habitat suitability layers in the WWHCS DST. Our objectives were to compare seasonal species distributions from habitat suitability models (expert‐derived) and species distribution models (eBird‐derived) and determine whether differences influenced DST prioritizations. Correlations between expert‐ and eBird‐derived distributions were generally low to moderate for breeding and fall layers (ρ: −0.03–0.76), and lowest for spring (ρ: −0.49–0.72). There was also minimal agreement among top‐ranked ecological landscapes (40%) and watersheds (28%) between the two versions of the DST. Finally, we compare tradeoffs and suggest a model‐driven approach for the WWHCS DST. However, additional work validating eBird relative abundance against professional surveys and empirical studies evaluating waterfowl habitat selection and vital rates are important future considerations for the DST and waterfowl habitat conservation in Wisconsin.